Fractionation of Arsenic in Soil by a Continuous‐Flow Sequential Extraction Method - Shiowatana, J.; McLaren, R. G.; Chanmekha, N.; Samphao, A. (Journal of environmental quality, 2001)
ABSTRACT Batch sequential extraction techniques for fractionating metals or metalloids in soils are time consuming and subject to several potential errors. The development of a continuous‐flow sequential extraction method for soil As is described and assessed, having the benefits of simplicity, rapidity, less risk of contamination, and less vulnerability to changes in extraction conditions compared with traditional batch methods. The validated method was used to fractionate soil As using water, NaHCO3, NaOH, and HCl, followed by digestion of the residue with HNO3 and HF acids. The extracts and digests were analyzed for As by graphite furnace atomic absorption spectrometry. Good recoveries of total soil As (97–115%) were obtained and fractionation data generally comparable with those obtained using conventional batch techniques. Soils from a tin‐mining area in Thailand and soils from As‐contaminated cattle (Bos taurus) dip sites in Australia were used to test the applicability of the method, and to demonstrate the usefulness of the extractogram obtained. The ability to produce detailed extractograms for As and other elements (Al, Fe, and Ca) enabled an examination of elemental associations in individual fractions. With the exception of As extracted with HCl, the extractograms generally support previous suggestions of the likely forms or associations of As present in the different soil fractions.